Patomechanisms in proliferative vitreoretinopathy - Kaczmarek, Radosław; Misiuk-Hojło, Marta (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
Proliferative vitreoretinopathy (PVR) remains the most common cause of recurrent retinal detachment following retinal detachment surgery. The development of PVR is a complex process involving humoral and cellular factors. Surgical treatment of PVR, which consists of removal of the fibrous membranes and restoration of physiological anatomic ocular conditions is often unsuccessful. Therefore the surgery should by backed up by local medication to inhibit new formation of proliferative lesions. Unfortunately, there is no satisfactory antiproliferative treatment available so far. Proliferative vitreoretinopathy remains a therapeutic challenge.